E-Learning in Increasing Student Motivation - vina umah (Language-Edu, 2021)
E-learning is a tool learning that is carried out through a network (computer network), usually via the internet or intranet. E-learning brings a change in the learning process from being centred on teaching to centring on learners or students. That is one of the learning strategies that allow students to access learning material anywhere and anytime (Munir, 2009:107).E-learning makes it easy for students to get lesson information because it is easier to access it anywhere. Teaching and learning processes are no longer dependent on location and time and can increase the motivation of learning teachers and students so that the learning process becomes more dynamic, flexible, interactive and communicative. (Jin.K:2013)Motivation and learning are two things that influence each other. Learning motivation can arise due to intrinsic and extrinsic factors caused by specific factors such as the desire and desire to succeed, and the urge of learning need. The hope for ideas. While the extrinsic factor is the existence of appreciation, a conducive learning environment and exciting learning activities. (Uno, 2001)Keywords: E-Learning, Motivation